Disseminated Medulloblastoma in a Child with Germline BRCA2 6174delT Mutation and without Fanconi Anemia - Xu, Jingying; Margol, Ashley Sloane; Shukla, Anju; Ren, Xiuhai; Finlay, Jonathan L.; Krieger, Mark D.; Gilles, Floyd H.; Couch, Fergus J.; Aziz, Meraj; Fung, Eric T.; Asgharzadeh, Shahab; Barrett, Michael T.; et al. (Frontiers in Oncology, 2015)
Medulloblastoma, the most common malignant brain tumor in children, occurs with increased frequency in individuals with Fanconi anemia who have biallelic germline mutations in BRCA2. We describe an 8 year old child who had disseminated anaplastic medulloblastoma and a deleterious heterozygous BRCA2 6174delT germline mutation. Molecular profiling was consistent with Group 4 medulloblastoma. The posterior fossa mass was resected and the patient received intensive chemotherapy and craniospinal irradiation. Despite this, the patient succumbed to a second recurrence of his medulloblastoma, which presented eight months after diagnosis as malignant pleural and peritoneal effusions. Continuous medulloblastoma cell lines were isolated from the original tumor (CHLA-01-MED) and the malignant pleural effusion (CHLA-01R-MED). Here we provide their analyses, including in vitro and in vivo growth, drug sensitivity, comparative genomic hybridization and next generation sequencing analysis. In addition to the BRCA2 6174delT, the medulloblastoma cells had amplification of MYC, deletion at Xp11.2 and isochromosome 17, but no structural variations or overexpression of GFI1 or GFI1B. To our knowledge, this is the first pair of diagnosis/recurrence medulloblastoma cell lines, the only medulloblastoma cell lines with BRCA2 6174delT described to date, and the first reported case of a child with medulloblastoma associated with a germline BRCA2 6174delT who did not also have Fanconi anemia.